Ecologia trófica de larvas de peixes neotropicais : interações intra e interespecíficas e relação predador-presa. - Rosa, Rafael Rogério (2021)
The survival and growth of fish larvae during ontogeny are related to the ability to obtain adequate food, providing subsidies for individuals reach the adult age. The foraging capacity, availability and abundance of prey and morphological development, especially swimming performance and visual acuity are important factors in reproductive success. In this study, the aspects related to feeding during the ontogeny of fish larvae from a floodplain system were analyzed, evaluating the coexistence capacity and the predator-prey interaction. Specifically, the objectives were (1) to analyze the inter and intraspecific variations in the diet of three invasive fish species (Auchenipterus osteomystax, Plagioscion squamosissimus and Hypophthalmus oremaculatus) during their initial ontogeny and the relationship with coexistence; and (2) to apply a new approach in trophic ecology studies during ontogeny, evaluating the interaction and organization of the predator-prey network, using A. osteomystax as model. The larvae of invasive fish species had different diets inter and intraspecifically, low diet overlap and high niche breadth primarily for P. squamosissimus. The coexistence of larvae of these species is probably possible due to low competition, differentiation of trophic guilds, resource partitioning and trophic plasticity. Regarding the predator-prey network, A. osteomystax showed a nested structure, low connectivity and a pattern of segregation in resource consumption. The larvae fed exclusively on aquatic insects, impacting the robustness of the network when the most frequent prey in the diet is removed, here represented by Diptera and Chironomidae pupa. Furthermore, the correlation between metric variables and morphological networks showed that the species is of more general position as the network develops, increasing its capacity predation. Both studies demonstrated the importance of knowing the species-habitat interaction and the processes that govern prey capture, avoiding inter and intraspecific competition through resource partitioning and behavioral and foraging changes during ontogeny.